Knowledge management: the tool of the conceptual map in the evaluation of a seminar on safety and security - Fernando Barcellos Razuck; FRANCISCO CESAR DA SILVA (Brazilian Journal of Radiation Sciences, 2020)
Introduction It can be said that the population, in general, has already heard or even used equipment that involvesthe issue of Nuclear Energy. However, the majority of the population does not understand the effects generated by Nuclear Energy on living organisms, especially on humans, thus showing the need to build a more accurate and informed knowledge about radiation in a formal learning situation. Therefore, there is a growing need for the nuclear area to promote a more open dialogue with the public, increasing public acceptance, mainly due to the fact that it is a risk technology [1]. Therefore, all risk technology refers to risk communication, which is directly associated with risk perception, considering the difference between how the risk is perceived by the public versus how the risk is effectively assessed and measured by the specialists. In fact, the purpose of risk communication is not to force a shift between the divergent views of the specialist and the public, but it is a matter of developing an understanding of these factors so that they can be considered and treated [2]. One possibility that opens to realize this communication of risk, as well as for a better understanding of the uses of Nuclear Energy, would be through Knowledge Management (CG). This is because the CG has been applied in order to create the necessary conditions for greater access to communication in a clear and rich way. Therefore, knowledge management aims to promote an integrated approach to identifying, capturing, evaluating, retrieving and sharing information, which in this case may be databases, documents, policies, procedures and an institution [3]. The tool in question was the Conceptual Map. Conceptual Maps are a tool that can gather knowledge of individuals and groups, facilitate the process of knowledge creation, function as a means of discussion and communication, and help in the distribution of knowledge and learning processes within an organization [4].